ANALISIS PERBEDAAN MOTIVASI KERJA, LOYALITAS KERJA, DAN KINERJA GURU YANG BERSERTIFIKASI DENGAN YANG BELUM BERSERTIFIKASI KECAMATAN KEDAWUNG SRAGEN - Ernawati, Gunardi, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2016)
The objective of the research are to analiysing significance difference of the work motivation, work loyalty, and teacher performance between certified teachers with non certified teachers in SDN Kecamatan Kedawung. Samples of this study are 146 teachers in public primary schools at district of Kedawung consists of 124 certified teachers and 22 non certified teachers, using technique of the propotionate stratified random sampling. Data collecting conducted by questioner, interview and documentation. Technique analyse the data using independent sample T-test. Based on the results of testing each hypothesis we concluded (1) there are significant differences of the work motivation between certified teacher with non certified teachers, means Ha.1 accepted. (2) there are significant differences of the work loyalty between certified teachers with non certified teachers, means Ha.2 accepted. (3) there are significant differences of the teacher performance between certified teachers with non certified teachers, means Ha.3 accepted. (4) the results of comparison mean statistics show that certified teachers have work motivation, job loyalty, and teacher performances are higher than non certified teachers.Keywords: work motivation, work loyality, teacher performance